SPIRITUALITAS ECKHART “SUNDER WARUMBE PADA TOKOH HENDRA” MENCINTAI TANPA MENGAPA? DALAM NOVEL “MY IDIOT BROTHER” KARYA AGNES DAVONAR - Doys Ivone (TANGKOLEH PUTAI, 2020)
Everyone has a different spiritual experience, including how to love someone or something. People who love others mostly have a background in the interests of giving each other. Therefore, there are those who easily understand the meaning of love and fight for and share love easily, but there are also those who experience the opposite. This paper focuses on one of the works of Agnes Davonar in the novel "My Idiot Brother" to understand Echart's experience of spirituality in the relationship between brothers and sisters, how to love someone without why. This writing uses mystical theology in understanding Echart's spirituality, namely the sunder warumbe of the Hendra character in the book.